Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The evolution of the cave's entrance of Bruniquel and consequences for its accessibility by early Homo neanderthalensis - K. Génuite; S. Verheyden; H. Camus; C. Burlet; M. Boudadi-Maligne; L. Bruxelles; H. Cheng; D. Cochard; S. Delaby; E. Fabre; C. Ferrier; C. Lézin; et al. (Quaternary Science Reviews, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Solvent-based synthesis and characterization of sodium thiophosphate catholytes for nonaqueous redox flow batteries - Ernesto C. Zuleta S.; Vaidyanathan Sethuraman; Michelle L. Lehmann; Gabriel Goenaga; Guang Yang; Lei Cheng; Ethan C. Self (Chemical Engineering Journal, 2026)

From digital decision-support to policy implementation: An operational framework for agri-environmental schemes - A.C. Wartenberg; C. Cheng; C. Marples; H. Dettmann; K. Hemminger; F. Ghafarian; L. Schaan; M. Scoville; S.D. Bellingrath-Kimura (Biological Conservation, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Identifying Headwater Streams across the Conterminous United States - Charles R. Lane; Ellen D’Amico; Jay R. Christensen; Heather E. Golden; Frederick Y. Cheng; John C. Hammond; Admin Husic; Kristin L. Jaeger; C. Nathan Jones; Christa A. Kelleher; Li Li; D. Tyler Mahoney; et al. (Ecosystems, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Spatial and temporal variations in the distribution of eastern Australian post-orogenic granites and related mineral deposits: metallogenic and tectonic significance - D. L. Huston; Y. Cheng; S. L. Jones; D. C. Champion; M. D. Norman; M. W. Agnew; A. Cross; V. C. Bennett; R. A. Creaser (Australian Journal of Earth Sciences, 2026)

Mesenchymal cell-derived extracellular vesicles ameliorate age-related deficits in working memory and in vivo MRI measures of white matter structure and function in rhesus monkeys - Evan C. Mackie; Chia-Hsin Cheng; Maya N. Alibrio; Christine Rutledge; Hongqi Xin; Michael Chopp; Ryan P. McCann; Douglas L. Rosene; Qiong Yang; Ella Zeldich; Maria Medalla; Bang-Bon Koo; et al. (GeroScience, 2025)
Aging humans and non-human primates both exhibit a similar pattern of cognitive decline beginning in middle age that is characterized by progressive impairments in rule learning, executive function, and working and recognition memory—functions often associated with dysfunction of prefrontal and medial temporal lobe regions. The heterogeneity and inter-subject variability in aging and age-related cognitive impairments present challenges for developing effective therapeutics and can be attributed to differing degrees of cortical white matter (WM) damage and alterations to local and long-range prefrontal and temporal networks. A promising therapeutic that has been shown to be efficacious in mitigating WM damage and improving cognitive function in rodent models is mesenchymal cell-derived extracellular vesicles (MSC-EVs). In the present study, late middle-aged rhesus monkeys were systemically administered monkey-derived MSC-EVs every 2 weeks for 18 months. We demonstrate that MSC-EV treatment improves spatial working memory and decreases the frequency of perseverative responses with largely no effects on recognition memory. These cognitive improvements were associated with increases in MRI diffusion measures of WM structural integrity over time as well as preservation of inter-network functional connectivity as measured by resting-state functional MRI. These findings suggest that MSC-EV treatment can slow or reverse age-related cognitive decline while strengthening WM integrity and improving functional connectivity in late middle-aged rhesus monkeys.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

The coupling between monsoon rainfall and Sea Surface Temperature in the subtropical South Atlantic during the Last Glacial Period - Lucas C. Vasconcelos; Francisco W. Cruz; Juan Pablo Bernal; Marília C. Campos; Patrícia Piacsek; José L. Campos; Haiwei Zhang; Nicolás Stríkis; Mathias Vuille; Giselle Utida; Christian Millo; R. Lawrence Edward; et al. (Global and Planetary Change, 2025)

Aqueous lead removal using biochar-pumice filter derived from avocado seed, aspen bedding and palm tree frond - V. Igberase; J. Parsons; C.-L. Cheng; J. Kim; J. J. Kang (International Journal of Environmental Science and Technology, 2025)

P30-01 Application of 3Rs Strategies for Existing Chemicals Substances Standard Registration in Taiwan: Case study of Silicon carbide - S.-N. Chen; O. Lautan; Y.-Y. Chen; Y.-L. Yeh; Y.-H. Cheng; C.-C. Tseng; T.-N. Li; Z.-Y. Chen; R.-J. Chen; Y.-J. Wang (Toxicology Letters, 2025)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

Fast arc retreat in the eastern Mediterranean: constraints from late Campanian forearc deposits (Donousa, Greece) - S. O. Martha; P. Xypolias; C. Cheng; W. Dörr; A. Gerdes; D. C. Hezel; M. Kutzschbach; L. Millonig; H. Schmeling; H. R. Marschall; W. Müller; G. Zulauf (International Journal of Earth Sciences, 2025)
The island of Donousa consists of a variegated metasedimentary sequence cut by arc-type granitoid dykes. Detrital zircon U–Pb ages and the presence of volcanic and ultramafic detritus suggest that the protoliths of the metasedimentary rocks were deposited in a Campanian forearc basin later than 76 Ma. D1 stacking of the forearc deposits occurred at upper crustal levels (P max = 0.4 GPa) with staurolite present as a stable phase. The subsequent isobaric heating led to growth of andalusite followed by D2 extension in the stability field of sillimanite, K-feldspar and high-quartz ( P = 0.3 GPa, T = 660 °C). Based on U–Pb ages of garnet (74.6 + 2.3/ − 2.5 Ma) and zircon (74.0 ± 0.8 Ma), separated from an early monzogranite dyke, the timing of forearc deposition, Buchan metamorphism, D2 extension and dyke emplacement is constrained to a maximum period of 2.6 m.y. in the late Campanian. Cooling below T = ca. 600 °C occurred during the Maastrichtian (71.3 + 0.6/ − 1.3 Ma, U–Pb on titanite) and was followed by D3 folding under greenschist facies conditions. A younger generation of Danian granitoid dykes (64.1 + 0.9/ − 1.4 Ma, U–Pb on titanite; 60 ± 4 Ma, Rb–Sr on muscovite) intruded at higher structural levels and was associated with a pervasive fluid-assisted overprint. The sequence of forearc deposition, burying, Buchan metamorphism, extension, and igneous dyking within < 2.6 m.y. is strong evidence for fast (ca. 4 cm a −1 ) trenchward arc retreat that was probably related to late Campanian subduction accretion and magmatic flare-up. Graphical abstract

Developing an integrated CO2 capture and mineralization process with lower energy consumption - K. H. Tham; T. Seah; Q. Y. Kouk; W. Goh; S. Cheng; C. Wang; J. Bu; L. Tao (International Journal of Energy and Water Resources, 2025)

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Impact thermal and calcium oxide pretreatment on the anaerobic digestion of food waste: performance and carbon emissions - Y. Liu; L. Tian; W. Qiu; W. Sun; C. Pan; G. Fan; Q. Cheng (International Journal of Environmental Science and Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

North Atlantic Heat Transport Convergence Derived from a Regional Energy Budget Using Different Ocean Heat Content Estimates - B. Meyssignac; S. Fourest; Michael Mayer; G. C. Johnson; F. M. Calafat; M. Ablain; T. Boyer; L. Cheng; D. Desbruyères; G. Forget; D. Giglio; M. Kuusela; et al. (Surveys in Geophysics, 2024)
This study uses an oceanic energy budget to estimate the ocean heat transport convergence in the North Atlantic during 2005–2018. The horizontal convergence of the ocean heat transport is estimated using ocean heat content tendency primarily derived from satellite altimetry combined with space gravimetry. The net surface energy fluxes are inferred from mass-corrected divergence of atmospheric energy transport and tendency of the ECMWF ERA5 reanalysis combined with top-of-the-atmosphere radiative fluxes from the clouds and the Earth’s radiant energy system project. The indirectly estimated horizontal convergence of the ocean heat transport is integrated between the rapid climate change-meridional overturning circulation and heatflux array (RAPID) section at 26.5°N (operating since 2004) and the overturning in the subpolar north atlantic program (OSNAP) section, situated at 53°–60°N (operating since 2014). This is to validate the ocean heat transport convergence estimate against an independent estimate derived from RAPID and OSNAP in-situ measurements. The mean ocean energy budget of the North Atlantic is closed to within ± 0.25 PW between RAPID and OSNAP sections. The mean oceanic heat transport convergence between these sections is 0.58 ± 0.25 PW, which agrees well with observed section transports. Interannual variability of the inferred oceanic heat transport convergence is also in reasonable agreement with the interannual variability observed at RAPID and OSNAP, with a correlation of 0.54 between annual time series. The correlation increases to 0.67 for biannual time series. Other estimates of the ocean energy budget based on ocean heat content tendency derived from various methods give similar results. Despite a large spread, the correlation is always significant meaning the results are robust against the method to estimate the ocean heat content tendency.

Pre-treatments to reduce metabolism in adult green-lipped mussel, Perna canaliculus, in preparation for live transportation - M. C. F. Cheng; L. N. Zamora; N. L. C. Ragg; A. J. R. Hickey; B. J. Dunphy (Aquaculture International, 2024)
Improved sustainability of aquaculture can be achieved by reducing product wastage post-harvest. Aquaculture of the green-lipped mussel, Perna canaliculus , is an important industry for New Zealand, which increasingly exports to live markets. Live transport can keep mussels fresh, but mussels could also be susceptible to handling stresses. To remedy this, pre-treatments that make mussels metabolically depressed, and thus potentially less sensitive to external stressors, were explored. As indicators of depressed metabolism, heart rate (HR), inferred cardiac output (PCO), and relative gaping magnitude (RGM) were simultaneously monitored in mussels experiencing different temperatures, dissolved oxygen levels and anaesthetic (MgCl 2 ) concentrations to compare their efficacy in inducing suppressed metabolism of adult P. canaliculus . We found complex interactions between HR, PCO, and RGM in response to these conditions; however, overall, these response variables were significantly correlated. Mussels showed depressed HR and PCO by up to 100% at 4 °C within 2 h, with correspondingly decreased RGM of up to 48%. Similarly, mussels immersed in 40 g L −1 MgCl 2 suppressed HR by up to 97%, accompanied by up to 76% decrease in PCO, and a slight increase in RGM (11%) after 2 h. While responses were variable, low DO levels suppressed HR by up to 50%, yet PCO and RGM increased two- and threefold relative to control groups. The results of the present study indicated that 4 °C and 40 g MgCl 2 L −1 were more effective conditions as pre-treatments than low dissolved oxygen lower the metabolism of P. canaliculus before live transport.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Creating Boundary Objects Supports Knowledge Co-development Processes: A Case Study Evaluation from the Colorado Front Range - Hannah L C Brown; Antony S Cheng; Nehalem C Clark; Andrew W Slack; Brett H Wolk (Journal of Forestry, 2024)
This qualitative case study evaluates manager and researcher perceptions of the impact of a place-based, collaborative knowledge co-development process and examines the outcomes of that co-development for changes to management approaches. The USDA Forest Service (Forest Service) Rocky Mountain Research Station General Technical Report 373 (GTR-373) is a codeveloped science synthesis that functions as a boundary object providing a framework for planning, designing, and implementing management action for restoration of ponderosa and dry mixed-conifer forests. The process of creating and socializing the GTR-373 framework fostered continual knowledge exchange and engagement between researchers and managers across different organizations and levels of decision-making. This built trust in the information, improved justification for management action, developed a common foundation for cross-boundary implementation, and increased communication. The framework has been applied across jurisdictions and has been used as a foundational tool for training staff and designing projects. However, adapting the GTR-373 framework across scales remains challenging. Study Implications: This qualitative case study evaluates a co-development process in which researchers and managers from multiple organizations and agencies collaborated to produce a science-informed restoration framework to support forest management on the Colorado Front Range (GTR-373). The process built trust, improved justification for management action, developed a common foundation for implementation, and increased communication. However, cross-boundary management across spatial scales remains challenging, and managers interpret information through organizational mandates and site-specific context. Sustained collaboration between researchers and land managers can help make science actionable and relevant at the appropriate scale for planning and management across expertise and jurisdictional boundaries.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Air quality improvement assessment and exposure risk of Shandong Province in China during 2014 to 2020 - N. N. Wang; C. Y. Zhu; Wei Li; M. Y. Qiu; B. L. Wang; X. Y. Li; B. D. Jiang; X. Y. Qu; Z. S. Li; H. C. Cheng (International Journal of Environmental Science and Technology, 2023)

Championing inclusive terminology in ecology and evolution - Susan J. Cheng; Kaitlyn M. Gaynor; Alex C. Moore; Kathy Darragh; Cesar O. Estien; J.W. Hammond; Christopher Lawrence; Kirby L. Mills; Marcella D. Baiz; Danielle Ignace; Lily Khadempour; Matthew A. McCary; et al. (Trends in Ecology & Evolution, 2023)

Meta‐analysis of ecosystem services associated with oyster restoration - Rachel S. Smith; Selina L. Cheng; Max C. N. Castorani (Conservation Biology, 2023)
Restoration of foundation species promises to reverse environmental degradation and return lost ecosystem services, but a lack of standardized evaluation across projects limits understanding of recovery, especially in marine systems. Oyster reefs are restored to reverse massive global declines and reclaim valuable ecosystem services, but the success of these projects has not been systematically and comprehensively quantified. We synthesized data on ecosystem services associated with oyster restoration from 245 pairs of restored and degraded reefs and 136 pairs of restored and reference reefs across 3500 km of U.S. Gulf of Mexico and Atlantic coastlines. On average, restoration was associated with a 21‐fold increase in oyster production (mean log response ratio = 3.08 [95% confidence interval: 2.58–3.58]), 34–97% enhancement of habitat provisioning (mean community abundance = 0.51 [0.41–0.61], mean richness = 0.29 [0.19–0.39], and mean biomass = 0.69 [0.39–0.99]), 54% more nitrogen removal (mean = 0.43 [0.13–0.73]), and 89–95% greater sediment nutrients (mean = 0.67 [0.27–1.07]) and organic matter (mean = 0.64 [0.44–0.84]) relative to degraded habitats. Moreover, restored reefs matched reference reefs for these ecosystem services. Our results support the continued and expanded use of oyster restoration to enhance ecosystem services of degraded coastal systems and match many functions provided by reference reefs.

Decolorization characteristics and mechanism of methyl orange dye by using Stenotrophomonas acidaminiphila EFS1 - C Yang; H Luo; W Cheng; K Jiang; L Lu; L Ling (International Journal of Environmental Science and Technology, 2022)

Coastal Vegetation and Bathymetry Influence Blue Crab Abundance Across Spatial Scales - Selina L. Cheng; Kinsey N. Tedford; Rachel S. Smith; Sean Hardison; Michael R. Cornish; Max C. N. Castorani (Estuaries and Coasts, 2022)
Blue crabs ( Callinectes sapidus ) are highly mobile, ecologically-important mesopredators that support multimillion-dollar fisheries along the western Atlantic Ocean. Understanding how blue crabs respond to coastal landscape change is integral to conservation and management, but such insights have been limited to a narrow range of habitats and spatial scales. We examined how local-scale to landscape-scale habitat characteristics and bathymetric features (channels and oceanic inlets) affect the relative abundance (catch per unit effort, CPUE) of adult blue crabs across a > 33 km 2 seagrass landscape in coastal Virginia, USA. We found that crab CPUE was 1.7 × higher in sparse (versus dense) seagrass, 2.4 × higher at sites farther from (versus nearer to) salt marshes, and unaffected by proximity to oyster reefs. The probability that a trapped crab was female was 5.1 × higher in sparse seagrass and 8 × higher near deep channels. The probability of a female crab being gravid was 2.8 × higher near seagrass meadow edges and 3.3 × higher near deep channels. Moreover, the likelihood of a gravid female having mature eggs was 16 × greater in sparse seagrass and 32 × greater near oceanic inlets. Overall, we discovered that adult blue crab CPUE is influenced by seagrass, salt marsh, and bathymetric features on scales from meters to kilometers, and that habitat associations depend on sex and reproductive stage. Hence, accelerating changes to coastal geomorphology and vegetation will likely alter the abundance and distribution of adult blue crabs, challenging marine spatial planning and ecosystem-based fisheries management.

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantifying cancer risk from exposures to medical imaging in the Risk of Pediatric and Adolescent Cancer Associated with Medical Imaging (RIC) Study: research methods and cohort profile - Marilyn L. Kwan; Diana L. Miglioretti; Erin J. A. Bowles; Sheila Weinmann; Robert T. Greenlee; Natasha K. Stout; Alanna Kulchak Rahm; Susan A. Alber; Priscila Pequeno; Lisa M. Moy; Carly Stewart; Cindy Fong; et al. (Cancer Causes & Control, 2022)

Severe introduced predator impacts despite attempted functional eradication - Brian S. Cheng; Jeffrey Blumenthal; Andrew L. Chang; Jordanna Barley; Matthew C. Ferner; Karina J. Nielsen; Gregory M. Ruiz; Chela J. Zabin (Biological Invasions, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Comparing the clinical outcomes across different sodium/glucose cotransporter 2 (SGLT2) inhibitors in heart failure patients: a systematic review and network meta-analysis of randomized controlled trials - Yao Hao Teo; Celine Shuen Yin Yoong; Nicholas L. Syn; Yao Neng Teo; Jia Yang Alex Cheong; Yoke-Ching Lim; Chi-Hang Lee; Tiong-Cheng Yeo; Ping Chai; Raymond C. C. Wong; Weiqin Lin; Ching-Hui Sia (European Journal of Clinical Pharmacology, 2021)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Evaluation of arsenic sorption performance using dendritic anatase and polycrystalline rutile nano-TiO2 for environmental applications - S. Yin; C.-L. Cheng; J. Parsons; Y. Mao; J. J. Kang; J. Kim (International Journal of Environmental Science and Technology, 2021)

Synthesis, structure-activity relationship studies and evaluation of a TLR 3/8/9 agonist and its analogues - Anindya Sarkar; Anushka C. Galasiti Kankanamalage; Qian Zhang; Heng Cheng; Prasanna Sivaprakasam; Joseph Naglich; Chunshan Xie; Sanjeev Gangwar; Dale L. Boger (Medicinal Chemistry Research, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Effects of some parameters on the removal of Cd(II) ions from aqueous solutions by polyethyleneimine–sodium xanthogenate - G. Wang; X. L. Cheng; Y. C. Zeng; Y. F. Jiang (International Journal of Environmental Science and Technology, 2020)

An integrated biophysical approach to discovering mechanisms of NDM-1 inhibition for several thiol-containing drugs - Sarah Fullington; Zishuo Cheng; Caitlyn Thomas; Callie Miller; Kundi Yang; Lin-Cheng Ju; Alexander Bergstrom; Ben A. Shurina; Stacey Lowery Bretz; Richard C. Page; David L. Tierney; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Ensemble Projections of Future Climate Change Impacts on the Eastern Bering Sea Food Web Using a Multispecies Size Spectrum Model - Jonathan C. P. Reum; Julia L. Blanchard; Kirstin K. Holsman; Kerim Aydin; Anne B. Hollowed; Albert J. Hermann; Wei Cheng; Amanda Faig; Alan C. Haynie; André E. Punt (Frontiers in Marine Science, 2020)

Lead removal from aqueous solutions using biochars derived from corn stover, orange peel, and pistachio shell - S. Mireles; J. Parsons; T. Trad; C.-L. Cheng; J. Kang (International Journal of Environmental Science and Technology, 2019)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

Thioredoxin overexpression in both the cytosol and mitochondria accelerates age-related disease and shortens lifespan in male C57BL/6 mice - Geneva M. Cunningham; Lisa C. Flores; Madeline G. Roman; Christie Cheng; Sara Dube; Colton Allen; Joseph M. Valentine; Gene B. Hubbard; Yidong Bai; Thomas L. Saunders; Yuji Ikeno (GeroScience, 2018)

Impact of individual and neighborhood factors on socioeconomic disparities in localized and advanced prostate cancer risk - Mindy C. DeRouen; Clayton W. Schupp; Juan Yang; Jocelyn Koo; Andrew Hertz; Salma Shariff-Marco; Myles Cockburn; David O. Nelson; Sue A. Ingles; Iona Cheng; Esther M. John; Scarlett L. Gomez (Cancer Causes & Control, 2018)

Bacteria and viruses in the nasopharynx immediately prior to onset of acute lower respiratory infections in Indigenous Australian children - Heidi C. Smith-Vaughan; Michael J. Binks; Jemima Beissbarth; Anne B. Chang; Gabrielle B. McCallum; Ian M. Mackay; Peter S. Morris; Robyn L. Marsh; Paul J. Torzillo; Danielle F. Wurzel; Keith Grimwood; Elizabeth Nosworthy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Statistical prediction of non‐Gaussian climate extremes in urban areas based on the first‐order difference method - Cheng Qian; Wen Zhou; Xiu‐Qun Yang; Johnny C. L. Chan (International Journal of Climatology, 2018)
Prediction of climate extremes is challenging, especially for non‐Gaussian extremes in urban areas where the majority of people live, since the Gaussian assumption used in linear regression is violated and the urbanization effect needs to be considered. In this study, the first‐order difference method is introduced to take these difficulties into account. Statistical prediction of the non‐Gaussian annual occurrence of hot days in downtown Hong Kong, which is highly urbanized, is used to illustrate this method. With the help of the first‐order difference of the annual occurrences, which follows a Gaussian distribution, the difference series is used as the predictant to find predictors and to construct a prediction model by using traditional linear regression. The difference is first predicted and is then added to the observed value at the preceding time to obtain the predicted annual occurrence. The historical urbanization effect is thus obtained directly from the observations at the preceding time. The prediction results are found desirable. The broad application potential and conditions in which this method should be used are also discussed.

Integrating Bayesian genomic cline analyses and association mapping of morphological and ecological traits to dissect reproductive isolation and introgression in a Louisiana Iris hybrid zone - Cheng‐Jung Sung; Katherine L. Bell; Chris C. Nice; Noland H. Martin (Molecular Ecology, 2018)
Hybrid zones provide unique opportunities to examine reproductive isolation and introgression in nature. We utilized 45,384 single nucleotide polymorphism ( SNP ) loci to perform association mapping of 14 floral, vegetative and ecological traits that differ between Iris hexagona and Iris fulva, and to investigate, using a Bayesian genomic cline ( BGC ) framework, patterns of genomic introgression in a large and phenotypically diverse hybrid zone in southern Louisiana. Many loci of small effect size were consistently found to be associated with phenotypic variation across all traits, and several individual loci were revealed to influence phenotypic variation across multiple traits. Patterns of genomic introgression were quite heterogeneous throughout the Louisiana Iris genome, with I. hexagona alleles tending to be favoured over those of I. fulva . Loci that were found to have exceptional patterns of introgression were also found to be significantly associated with phenotypic variation in a small number of morphological traits. However, this was the exception rather than the rule, as most loci that were associated with morphological trait variation were not significantly associated with excess ancestry. These findings provide insights into the complexity of the genomic architecture of phenotypic differences and are a first step towards identifying loci that are associated with both trait variation and reproductive isolation in nature.

Corticosteroids and aldose reductase inhibitor Epalrestat modulates cardiac action potential via Kvβ1.1 (AKR6A8) subunit of voltage-gated potassium channel - Jared Tur; Sachin L. Badole; Feng Cheng; Aparoop Das; Rakesh C. Kukreja; Srinivas M. Tipparaju (Molecular and Cellular Biochemistry, 2017)

Serum 25-hydroxyvitamin D concentrations and lung cancer risk in never-smoking postmenopausal women - Ting-Yuan David Cheng; Xiaoling Song; Shirley A. A. Beresford; Gloria Y. F. Ho; Karen C. Johnson; Mridul Datta; Rowan T. Chlebowski; Jean Wactawski-Wende; Lihong Qi; Marian L. Neuhouser (Cancer Causes & Control, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Timing of stressors alters interactive effects on a coastal foundation species - Jillian M. Bible; Brian S. Cheng; Andrew L. Chang; Matthew C. Ferner; Kerstin Wasson; Chela J. Zabin; Marilyn Latta; Eric Sanford; Anna Deck; Edwin D. Grosholz (Ecology, 2017)
The effects of climate‐driven stressors on organismal performance and ecosystem functioning have been investigated across many systems; however, manipulative experiments generally apply stressors as constant and simultaneous treatments, rather than accurately reflecting temporal patterns in the natural environment. Here, we assessed the effects of temporal patterns of high aerial temperature and low salinity on survival of Olympia oysters ( Ostrea lurida ), a foundation species of conservation and restoration concern. As single stressors, low salinity (5 and 10 psu) and the highest air temperature (40°C) resulted in oyster mortality of 55.8, 11.3, and 23.5%, respectively. When applied on the same day, low salinity and high air temperature had synergistic negative effects that increased oyster mortality. This was true even for stressor levels that were relatively mild when applied alone (10 psu and 35°C). However, recovery times of two or four weeks between stressors eliminated the synergistic effects. Given that most natural systems threatened by climate change are subject to multiple stressors that vary in the timing of their occurrence, our results suggest that it is important to examine temporal variation of stressors in order to more accurately understand the possible biological responses to global change.

Erratum to: Small RNAs from a Big Genome: The piRNA Pathway and Transposable Elements in the Salamander Species Desmognathus fuscus - M. J. Madison-Villar; Cheng Sun; Nelson C. Lau; Matthew L. Settles; Rachel Lockridge Mueller (Journal of Molecular Evolution, 2017)

Time Course Field Analysis of COMT-Downregulated Switchgrass: Lignification, Recalcitrance, and Rust Susceptibility - Holly L. Baxter; Mitra Mazarei; Chunxiang Fu; Qunkang Cheng; Geoffrey B. Turner; Robert W. Sykes; Mark T. Windham; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (BioEnergy Research, 2016)

Small RNAs from a Big Genome: The piRNA Pathway and Transposable Elements in the Salamander Species Desmognathus fuscus - M. J. Madison-Villar; Cheng Sun; Nelson C. Lau; Matthew L. Settles; Rachel Lockridge Mueller (Journal of Molecular Evolution, 2016)

Effects of Palygorskite Inclusion on the Growth Performance, Meat Quality, Antioxidant Ability, and Mineral Element Content of Broilers - Y. F. Cheng; Y. P. Chen; X. H. Li; W. L. Yang; C. Wen; Y. M. Zhou (Biological Trace Element Research, 2016)

Identifying microRNAs targeting Wnt/β-catenin pathway in end-stage idiopathic pulmonary arterial hypertension - Danchen Wu; C. Conover Talbot; Qun Liu; Zhi-Cheng Jing; Rachel L. Damico; Rubin Tuder; Kathleen C. Barnes; Paul M. Hassoun; Li Gao (Journal of Molecular Medicine, 2016)

Increased rodenticide exposure rate and risk of toxicosis in barn owls (Tyto alba) from southwestern Canada and linkage with demographic but not genetic factors - Andrew C. Huang; John E. Elliott; Sofi Hindmarch; Sandi L. Lee; France Maisonneuve; Victoria Bowes; Kimberly M. Cheng; Kathy Martin (Ecotoxicology, 2016)

Toxicity and in vitro activity of HIV-1 latency-reversing agents in primary CNS cells - Lachlan R. Gray; Hung On; Emma Roberts; Hao K. Lu; Michael A. Moso; Jacqueline A. Raison; Catherine Papaioannou; Wan-Jung Cheng; Anne M. Ellett; Jonathan C. Jacobson; Damian F. J. Purcell; Steve L. Wesselingh; et al. (Journal of NeuroVirology, 2016)

Characterization of a New Wheat- Aegilops biuncialis 1M b (1B) Substitution Line with Good Quality-associated HMW Glutenin Subunit - J. P. Zhou; Y. Cheng; L. L. Zang; E. N. Yang; C. Liu; X. L. Zheng; K. J. Deng; Y. Q. Zhu; Y. Zhang (Cereal Research Communications, 2016)

Characterization of carbapenem-resistant Escherichia coli and Klebsiella pneumoniae from a healthcare region in Hong Kong - P. L. Ho; Y. Y. Cheung; Y. Wang; W. U. Lo; E. L. Y. Lai; K. H. Chow; V. C. C. Cheng (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Three N-Glycosylation Sites of Human Acetylcholinesterase Shares Similar Glycan Composition - Miranda L. Xu; Wilson K. W. Luk; Kei M. Lau; Cathy W. C. Bi; Anthony W. M. Cheng; Amy G. W. Gong; Huangquan Lin; Karl W. K. Tsim (Journal of Molecular Neuroscience, 2015)

Use of fluoroquinolones is the single most important risk factor for the high bacterial load in patients with nasal and gastrointestinal colonization by multidrug-resistant Acinetobacter baumannii - V. C. C. Cheng; J. H. K. Chen; S. Y. C. So; S. C. Y. Wong; M. K. Yan; P. H. Chau; W. M. Lee; K. K. W. To; J. F. W. Chan; I. F. N. Hung; P. L. Ho; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Effect of norbinaltorphimine on ∆9-tetrahydrocannabinol (THC)-induced taste avoidance in adolescent and adult Sprague-Dawley rats - Shaun M. Flax; Alison G. P. Wakeford; Kejun Cheng; Kenner C. Rice; Anthony L. Riley (Psychopharmacology, 2015)

Performance of the new automated Abbott RealTime MTB assay for rapid detection of Mycobacterium tuberculosis complex in respiratory specimens - J. H. K. Chen; K. K. K. She; T.-C. Kwong; O.-Y. Wong; G. K. H. Siu; C.-C. Leung; K.-C. Chang; C.-M. Tam; P.-L. Ho; V. C. C. Cheng; K.-Y. Yuen; W.-C. Yam (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Historical and experimental evidence for enhanced concentration of artemesinin, a global anti-malarial treatment, with recent and projected increases in atmospheric carbon dioxide - C. Zhu; Q. Zeng; A. McMichael; K. L. Ebi; K. Ni; A. S. Khan; J. Zhu; G. Liu; X. Zhang; Lei Cheng; L.H. Ziska (Climatic Change, 2015)

Containment of Clostridium difficile infection without reduction in antimicrobial use in Hong Kong - V. C. C. Cheng; P. H. Chau; S. Y. C. So; J. H. K. Chen; R. W. S. Poon; S. C. Y. Wong; I. F. N. Hung; W. M. Lee; J. W. M. Tai; P. L. Ho; W. C. Yam; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Testing local and global stressor impacts on a coastal foundation species using an ecologically realistic framework - Brian S. Cheng; Jillian M. Bible; Andrew L. Chang; Matthew C. Ferner; Kerstin Wasson; Chela J. Zabin; Marilyn Latta; Anna Deck; Anne E. Todgham; Edwin D. Grosholz (Global Change Biology, 2015)
Despite the abundance of literature on organismal responses to multiple environmental stressors, most studies have not matched the timing of experimental manipulations with the temporal pattern of stressors in nature. We test the interactive effects of diel‐cycling hypoxia with both warming and decreased salinities using ecologically realistic exposures. Surprisingly, we found no evidence of negative synergistic effects on Olympia oyster growth; rather, we found only additive and opposing effects of hypoxia (detrimental) and warming (beneficial). We suspect that diel‐cycling provided a temporal refuge that allowed physiological compensation. We also tested for latent effects of warming and hypoxia to low‐salinity tolerance using a seasonal delay between stressor events. However, we did not find a latent effect, rather a threshold survival response to low salinity that was independent of early life‐history exposure to warming or hypoxia. The absence of synergism is likely the result of stressor treatments that mirror the natural timing of environmental stressors. We provide environmental context for laboratory experimental data by examining field time series environmental data from four North American west coast estuaries and find heterogeneous environmental signals that characterize each estuary, suggesting that the potential stressor exposure to oysters will drastically differ over moderate spatial scales. This heterogeneity implies that efforts to conserve and restore oysters will require an adaptive approach that incorporates knowledge of local conditions. We conclude that studies of multiple environmental stressors can be greatly improved by integrating ecologically realistic exposure and timing of stressors found in nature with organismal life‐history traits.

The RIG-I-like helicase receptor MDA5 (IFIH1) is involved in the host defense against Candida infections - M. Jaeger; R. van der Lee; S.-C. Cheng; M. D. Johnson; V. Kumar; A. Ng; T. S. Plantinga; S. P. Smeekens; M. Oosting; X. Wang; W. Barchet; K. Fitzgerald; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Control of hospital endemicity of multiple-drug-resistant Acinetobacter baumannii ST457 with directly observed hand hygiene - V. C. C. Cheng; J. H. K. Chen; R. W. S. Poon; W. M. Lee; S. Y. C. So; S. C. Y. Wong; P. H. Chau; C. C. Y. Yip; S. S. Y. Wong; J. F. W. Chan; I. F. N. Hung; P. L. Ho; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Mapping QTLs of caudal fin length in common carp ( Cyprinus carpio L.) - C Lu; Y Zhang; X Zheng; X Zhang; C Li; Y Kuang; D Cao; L Cheng; G Qiu; X Sun (New Zealand Journal of Marine and Freshwater Research, 2015)
Common carp ( Cyprinus carpio L.) exhibits significant morphological variability in the shape and size of the caudal fin. In this study, we used 190 progeny from two F 1 parents to identify and map quantitative trait loci (QTLs) that influence caudal fin length ( CFL ) and the ratio ( RCS ) between caudal fin length and standard length ( SL ) based on a microsatellite genetic map of common carp. A total of 15 QTLs were detected in seven different linkage groups. One significant and eight suggestive QTLs affecting CFL were identified on LG8, LG14, LG29, LG32 and LG44, which explained 8.0%–22.1% of the phenotypic variation; six suggestive QTLs affecting RCS were detected on LG8, LG32, LG46 and LG48, which explained 7.0%–15.4% of the phenotypic variation. The QTLs for caudal fin length detected in this study may serve as a starting point for identification of genes involved in caudal fin development in common carp.

Development and characterization of two monoclonal antibodies against grouper iridovirus 55L and 97L proteins - S‐L Hu; C‐J Liou; Y‐H Cheng; J‐C Yiu; P P Chiou; Y‐S Lai (Journal of Fish Diseases, 2015)
Grouper iridovirus (GIV) is one of the most important viral pathogens in grouper, particularly at the fry and fingerling stages. The study of GIV pathogenicity has been hampered by the lack of proper immunological reagents to study the expression and function of viral proteins in the infected cells. In this study, two mouse monoclonal antibodies ( mA bs) against GIV 55L and 97L proteins were produced. Enzyme‐linked immunosorbent assay (ELISA) and Western blotting were used to screen these hybridomas, resulting in the identification of two high‐affinity mA bs named GIV55L‐ mA b‐2 and GIV97L‐ mA b‐3, respectively. Both mA bs belong to the IgG1 isotype and were effective in detecting their respective target viral protein. Reverse‐transcription polymerase chain reaction (RT‐PCR) and Western blot analyses of GIV‐infected GK cells revealed that GIV 97L is an immediate early gene, whereas GIV 55L a late one. The localization of 55L and 97L in GIV‐infected cells was further characterized by immunofluorescence microscopy with the mA bs. The 55L protein mainly aggregated in the cytoplasm while 97L distributed in both the nucleus and cytoplasm of the infected cells. These studies demonstrate the validity of the two mA bs as immunodiagnostic and research reagents.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

A Solution for Flood Control in Urban Area: Using Street Block and Raft Foundation Space Operation Model - Y. C. Liu; C. L. Cheng (Water Resources Management, 2014)

Structural integrity affects nitrogen removal activity of granules in semi-continuous reactors - Cesar R. Mota; Melanie A. Head; Jon C. Williams; Lucy Eland; Jay J. Cheng; Francis L. de los Reyes (Biodegradation, 2014)

The hidden history of the snowshoe hare, L epus americanus : extensive mitochondrial DNA introgression inferred from multilocus genetic variation - José Melo‐Ferreira; Fernando A. Seixas; Ellen Cheng; L. Scott Mills; Paulo C. Alves (Molecular Ecology, 2014)
Hybridization drives the evolutionary trajectory of many species or local populations, and assessing the geographic extent and genetic impact of interspecific gene flow may provide invaluable clues to understand population divergence or the adaptive relevance of admixture. In N orth A merica, hares ( L epus spp.) are key species for ecosystem dynamics and their evolutionary history may have been affected by hybridization. Here we reconstructed the speciation history of the three most widespread hares in N orth A merica – the snowshoe hare ( L epus americanus ), the white‐tailed jackrabbit ( L . townsendii ) and the black‐tailed jackrabbit ( L . californicus ) – by analysing sequence variation at eight nuclear markers and one mitochondrial DNA (mt DNA ) locus (6240 bp; 94 specimens). A multilocus–multispecies coalescent‐based phylogeny suggests that L . americanus diverged ~2.7 Ma and that L . californicus and L . townsendii split more recently (~1.2 Ma). Within L . americanus, a deep history of cryptic divergence (~2.0 Ma) was inferred, which coincides with major speciation events in other N orth A merican species. While the isolation‐with‐migration model suggested that nuclear gene flow was generally rare or absent among species or major genetic groups, coalescent simulations of mt DNA divergence revealed historical mt DNA introgression from L . californicus into the P acific N orthwest populations of L . americanus . This finding marks a history of past reticulation between these species, which may have affected other parts of the genome and influence the adaptive potential of hares during climate change.

Conservation implications of the evolutionary history and genetic diversity hotspots of the snowshoe hare - Ellen Cheng; Karen E. Hodges; José Melo‐Ferreira; Paulo C. Alves; L. Scott Mills (Molecular Ecology, 2014)
With climate warming, the ranges of many boreal species are expected to shift northward and to fragment in southern peripheral ranges. To understand the conservation implications of losing southern populations, we examined range‐wide genetic diversity of the snowshoe hare ( Lepus americanus ), an important prey species that drives boreal ecosystem dynamics. We analysed microsatellite (8 loci) and mitochondrial DNA sequence (cytochrome b and control region) variation in almost 1000 snowshoe hares. A hierarchical structure analysis of the microsatellite data suggests initial subdivision in two groups, Boreal and southwestern. The southwestern group further splits into Greater Pacific Northwest and U.S. Rockies. The genealogical information retrieved from mt DNA is congruent with the three highly differentiated and divergent groups of snowshoe hares. These groups can correspond with evolutionarily significant units that might have evolved in separate refugia south and east of the Pleistocene ice sheets. Genetic diversity was highest at mid‐latitudes of the species' range, and genetic uniqueness was greatest in southern populations, consistent with substructuring inferred from both mt DNA and microsatellite analyses at finer levels of analysis. Surprisingly, snowshoe hares in the Greater Pacific Northwest mt DNA lineage were more closely related to black‐tailed jackrabbits (Lepus californicus ) than to other snowshoe hares, which may result from secondary introgression or shared ancestral polymorphism. Given the genetic distinctiveness of southern populations and minimal gene flow with their northern neighbours, fragmentation and loss of southern boreal habitats could mean loss of many unique alleles and reduced evolutionary potential.

Effects of Parkinson’s disease on optic flow perception for heading direction during navigation - Cheng-Chieh Lin; Robert C. Wagenaar; Daniel Young; Elliot L. Saltzman; Xiaolin Ren; Sandy Neargarder; Alice Cronin-Golomb (Experimental Brain Research, 2014)

Influence of Unloading Rate on the Strainburst Characteristics of Beishan Granite Under True-Triaxial Unloading Conditions - X. G. Zhao; J. Wang; M. Cai; C. Cheng; L. K. Ma; R. Su; F. Zhao; D. J. Li (Rock Mechanics and Rock Engineering, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Optimism and Challenge for Science‐Based Conservation of Migratory Species in and out of U.S. National Parks - JOEL BERGER; STEVEN L. CAIN; ELLEN CHENG; PETER DRATCH; KEVIN ELLISON; JOHN FRANCIS; HERBERT C. FROST; SCOTT GENDE; CRAIG GROVES; WILLIAM A. KARESH; ELAINE LESLIE; GARY MACHLIS; et al. (Conservation Biology, 2014)
Public agencies sometimes seek outside guidance when capacity to achieve their mission is limited. Through a cooperative agreement and collaborations with the U.S. National Park Service (NPS), we developed recommendations for a conservation program for migratory species. Although NPS manages ∼36 million hectares of land and water in 401 units, there is no centralized program to conserve wild animals reliant on NPS units that also migrate hundreds to thousands of kilometers beyond parks. Migrations are imperiled by habitat destruction, unsustainable harvest, climate change, and other impediments. A successful program to counter these challenges requires public support, national and international outreach, and flourishing migrant populations. We recommended two initial steps. First, in the short term, launch or build on a suite of projects for high‐profile migratory species that can serve as proof to demonstrate the centrality of NPS units to conservation at different scales. Second, over the longer term, build new capacity to conserve migratory species. Capacity building will entail increasing the limited knowledge among park staff about how and where species or populations migrate, conditions that enable migration, and identifying species’ needs and resolving them both within and beyond parks. Building capacity will also require ensuring that park superintendents and staff at all levels support conservation beyond statutory borders. Until additional diverse stakeholders and a broader American public realize what can be lost and do more to protect it and engage more with land management agencies to implement actions that facilitate conservation, long distance migrations are increasingly likely to become phenomena of the past. Optimismo y Retos para la Conservación Científicamente Basada de Especies Migratorias Dentro y Fuera de Parques Nacionales de E.U.A.

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population - Logan Dumitrescu; Cara L. Carty; Nora Franceschini; Lucia A. Hindorff; Shelley A. Cole; Petra Bůžková; Fredrick R. Schumacher; Charles B. Eaton; Robert J. Goodloe; David J. Duggan; Jeff Haessler; Barbara Cochran; et al. (Human Genetics, 2013)

The association between pro-inflammatory cytokines, regional cerebral metabolism, and cognitive complaints following adjuvant chemotherapy for breast cancer - K. L. Pomykala; P. A. Ganz; J. E. Bower; L. Kwan; S. A. Castellon; S. Mallam; I. Cheng; R. Ahn; E. C. Breen; M. R. Irwin; D. H. S. Silverman (Brain Imaging and Behavior, 2013)

White spot syndrome virus epizootic in cultured P acific white shrimp L itopenaeus vannamei (Boone) in T aiwan - L Cheng; W‐H Lin; P‐C Wang; M‐A Tsai; J‐P Hsu; S‐C Chen (Journal of Fish Diseases, 2013)
White spot syndrome virus ( WSSV ) has caused significant losses in shrimp farms worldwide. Between 2004 and 2006, Pacific white shrimp L itopenaeus vannamei (Boone) were collected from 220 farms in T aiwan to determine the prevalence and impact of WSSV infection on the shrimp farm industry. Polymerase chain reaction ( PCR ) analysis detected WSSV in shrimp from 26% of farms. Juvenile shrimp farms had the highest infection levels (38%; 19/50 farms) and brooder shrimp farms had the lowest (5%; one of 20 farms). The average extent of infection at each farm was as follows for WSSV ‐positive farms: post‐larvae farms, 71%; juvenile farms, 61%; subadult farms, 62%; adult farms, 49%; and brooder farms, 40%. Characteristic white spots, hypertrophied nuclei and basophilic viral inclusion bodies were found in the epithelia of gills and tail fans, appendages, cephalothorax and hepatopancreas, and virions of WSSV were observed. Of shrimp that had WSSV lesions, 100% had lesions on the cephalothorax, 96% in gills and tail fans, 91% on appendages and 17% in the hepatopancreas. WSSV was also detected in copepoda and crustaceans from the shrimp farms. Sequence comparison using the pms146 gene fragment of WSSV showed that isolates from the farms had 99.7–100% nucleotide sequence identity with four strains in the G en B ank database – China ( AF332093 ), T aiwan ( AF440570 and U50923 ) and Thailand ( AF369029 ). This is the first broad study of WSSV infection in L . vannamei in T aiwan.

Characterization of a novel cell line from the caudal fin of koi carp Cyprinus carpio - S.‐L. Lin; Y.‐H. Cheng; C.‐M. Wen; S.‐N. Chen (Journal of Fish Biology, 2013)
A continuous cell line ( KF ‐101) derived from the caudal fin of the koi carp Cyprinus carpio was established and characterized. The KF ‐101 cell line multiplied abundantly in Leibovitz's L‐15 medium containing 10% foetal bovine serum at 25° C, and was subcultured for >90 passages over a period of 3 years. Immunocytochemistry revealed that the KF ‐101 cells contain keratin, junction proteins connexin‐43 and occludin, and ectodermal stem‐cell marker Pax‐6, but not vimentin. Furthermore, the KF ‐101 cells reacted with anti‐human DARPP ‐32 and anti‐human GATA ‐4 antibodies, and the labelling was regulated according to the cell cycle. The labels of the DARPP ‐32 and GATA ‐4 antibodies in the KF ‐101 cells were the suggested phosphatase‐1 inhibitor‐1 and GATA ‐3, respectively. In addition, the KF ‐101 cells were susceptible to koi herpesvirus but were resistant to eel herpesvirus, iridovirus, grouper nodavirus and chum salmon ( Oncorhynchus keta ) virus. The results indicate that the KF ‐101 cells are suitable materials for investigating biological and virological development.

Levels, seasonal variations, and health risks assessment of ambient air pollutants in the residential areas - W. C. Zhao; J. P. Cheng; Z. Y. Yu; Q. L. Tang; F. Cheng; Y. W. Yin; W. H. Wang (International Journal of Environmental Science and Technology, 2013)

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Molecular diversity of bacteria in Yunnan yellow cattle (Bos taurs) from Nujiang region, China - J. Leng; Y. M. Cheng; C. Y. Zhang; R. J. Zhu; S. L. Yang; X. Gou; W. D. Deng; H. M. Mao (Molecular Biology Reports, 2012)

GPS radio occultation measurements on ionospheric electron density from low Earth orbit - L.-C. Tsai; Kai-Chien Cheng; C. H. Liu (Journal of Geodesy, 2011)

Stress-induced reinstatement of alcohol-seeking in rats is selectively suppressed by the neurokinin 1 (NK1) antagonist L822429 - Jesse R. Schank; Charles L. Pickens; Kelly E. Rowe; Kejun Cheng; Annika Thorsell; Kenner C. Rice; Yavin Shaham; Markus Heilig (Psychopharmacology, 2011)

Clostridium difficile isolates with increased sporulation: emergence of PCR ribotype 002 in Hong Kong - V. C. C. Cheng; W. C. Yam; O. T. C. Lam; J. L. Y. Tsang; E. Y. F. Tse; G. K. H. Siu; J. F. W. Chan; H. Tse; K. K. W. To; J. W. M. Tai; P. L. Ho; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Sensitivity analysis of climatic parameters for sky classification - D. H. W. Li; H. L. Tang; K. L. Cheung; E. W. M. Lee; C. C. K. Cheng (Theoretical and Applied Climatology, 2011)

Hemodynamic Changes Quantified in Abdominal Aortic Aneurysms with Increasing Exercise Intensity Using MR Exercise Imaging and Image-Based Computational Fluid Dynamics - Ga-Young Suh; Andrea S. Les; Adam S. Tenforde; Shawn C. Shadden; Ryan L. Spilker; Janice J. Yeung; Christopher P. Cheng; Robert J. Herfkens; Ronald L. Dalman; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Quantification of Particle Residence Time in Abdominal Aortic Aneurysms Using Magnetic Resonance Imaging and Computational Fluid Dynamics - Ga-Young Suh; Andrea S. Les; Adam S. Tenforde; Shawn C. Shadden; Ryan L. Spilker; Janice J. Yeung; Christopher P. Cheng; Robert J. Herfkens; Ronald L. Dalman; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

A multi-modeling approach to evaluating climate and land use change impacts in a Great Lakes River Basin - M. J. Wiley; D. W. Hyndman; B. C. Pijanowski; A. D. Kendall; C. Riseng; E. S. Rutherford; S. T. Cheng; M. L. Carlson; J. A. Tyler; R. J. Stevenson; P. J. Steen; P. L. Richards; et al. (Hydrobiologia, 2010)

Oriented Markov Random Field Based Dendritic Spine Segmentation for Fluorescence Microscopy Images - Jie Cheng; Xiaobo Zhou; Eric L. Miller; Veronica A. Alvarez; Bernardo L. Sabatini; Stephen T. C. Wong (Neuroinformatics, 2010)

Falling-Edge, Variable Threshold (FEVT) Method for the Automated Detection of Gastric Slow Wave Events in High-Resolution Serosal Electrode Recordings - Jonathan C. Erickson; Gregory O’Grady; Peng Du; Chibuike Obioha; Wenlian Qiao; William O. Richards; L. Alan Bradshaw; Andrew J. Pullan; Leo K. Cheng (Annals of Biomedical Engineering, 2010)

Establishment, characterization, virus susceptibility and transfection of cell lines from cobia, Rachycentron canadum (L.), brain and fin - T‐C Cheng; Y‐S Lai; I‐Y Lin; C‐P Wu; S‐L Chang; T‐I Chen; M‐S Su (Journal of Fish Diseases, 2010)
Establishment and characterization of two cobia, Rachycentron canadum, cell lines derived from cobia brain (CB) and cobia fin (CF) are described. Caudal fin and brain from juvenile cobia were dissociated for 30 and 10 min, respectively, in phosphate‐buffered saline containing 0.25% trypsin at 25 °C. The optimal culture condition for both dissociated cells (primary cell culture) was at 28 °C in Leibovitz‐15 medium containing 10% foetal bovine serum. The cells have been sub‐cultured at a ratio of 1:2 for more than 160 passages over a period of 3 years. Origin of the cultured cells was verified by comparison of their sequences of mitochondrial cytochrome oxidase subunit I genes ( cox I ) with the cox 1 sequence from cobia muscle tissue. The cell lines showed polyploidy. No mycoplasma contamination was detected. Susceptibility to grouper iridovirus was observed for the CB cell line but not the CF cell line. Both cell lines expressed green fluorescent protein after being transfected with green fluorescent reporter gene driven by the cytomegalovirus promoter.

Antimicrobial stewardship program directed at broad-spectrum intravenous antibiotics prescription in a tertiary hospital - V. C. C. Cheng; K. K. W. To; I. W. S. Li; B. S. F. Tang; J. F. W. Chan; S. Kwan; R. Mak; J. Tai; P. Ching; P. L. Ho; W. H. Seto (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Effects of grape xylem sap and cell wall constituents on in vitro growth, biofilm formation and cellular aggregation of Xylella fastidiosa - Davis W. Cheng; Hong Lin; M. Andrew Walker; Drake C. Stenger; Edwin L. Civerolo (European Journal of Plant Pathology, 2009)

Genetic analysis of photoperiod sensitivity in a tropical by temperate maize recombinant inbred population using molecular markers - C. L. Wang; F. F. Cheng; Z. H. Sun; J. H. Tang; L. C. Wu; L. X. Ku; Y. H. Chen (Theoretical and Applied Genetics, 2008)

Transcriptional analysis of a major capsid protein gene from Spodoptera exigua ascovirus 5a - T. Z. Salem; C. M. Turney; L. Wang; J. Xue; X.-F. Wan; X.-W. Cheng (Archives of Virology, 2008)

Climate simulations for 1880–2003 with GISS modelE - J. Hansen; M. Sato; R. Ruedy; P. Kharecha; A. Lacis; R. Miller; L. Nazarenko; K. Lo; G. A. Schmidt; G. Russell; I. Aleinov; S. Bauer; et al. (Climate Dynamics, 2007)

Distribution of convection associated with tropical cyclones making landfall along the South China coast - K. S. Liu; J. C. L. Chan; W. C. Cheng; S. L. Tai; P. W. Wong (Meteorology and Atmospheric Physics, 2007)

Urinary levels of RANTES and M-CSF are predictors of lupus nephritis flare - S. Tian; J. Li; L. Wang; T. Liu; H. Liu; G. Cheng; D. Liu; Y. Deng; R. Gou; Y. Wan; J. Jia; C. Chen (Inflammation Research, 2007)

Electro-mechanical stability of surface EMG sensors - S. H. Roy; G. De Luca; M. S. Cheng; A. Johansson; L. D. Gilmore; C. J. De Luca (Medical & Biological Engineering & Computing, 2007)

The two giant sister species of the Southern Ocean, Dissostichus eleginoides and Dissostichus mawsoni, differ in karyotype and chromosomal pattern of ribosomal RNA genes - L. Ghigliotti; F. Mazzei; C. Ozouf-Costaz; C. Bonillo; R. Williams; C.-H. C. Cheng; E. Pisano (Polar Biology, 2007)

Developmental regulation of SSeCKS expression in rat brain - L. Chen; J. Qin; C. Cheng; H. Liu; J. Qian; L. Sun; F. Xiao; S. Shi; S. Niu; A. Shen (Journal of Molecular Neuroscience, 2007)

Src suppressed C kinase substrate regulates the lipopolysaccharide-induced TNF-α biosynthesis in rat astrocytes - L. -l. Sun; C. Cheng; H. -o. Liu; C. -c. Shen; F. Xiao; J. Qin; J. -l. Yang; A. -g. Shen (Journal of Molecular Neuroscience, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Analysis of candidate genes on chromosome 2 in oral cleft case-parent trios from three populations - T. H. Beaty; J. B. Hetmanski; M. D. Fallin; J. W. Park; J. W. Sull; I. McIntosh; K. Y. Liang; C. A. VanderKolk; R. J. Redett; S. A. Boyadjiev; E. W. Jabs; S. S. Chong; et al. (Human Genetics, 2006)

Activation of mitogen-activated protein kinases is essential for hydrogen peroxide -induced apoptosis in retinal pigment epithelial cells - T.-C. Ho; Y.-C. Yang; H.-C. Cheng; A.-C. Wu; S.-L. Chen; H.-K. Chen; Y.-P. Tsao (Apoptosis, 2006)

QTL analysis for rice grain length and fine mapping of an identified QTL with stable and major effects - X. Y. Wan; J. M. Wan; L. Jiang; J. K. Wang; H. Q. Zhai; J. F. Weng; H. L. Wang; C. L. Lei; J. L. Wang; X. Zhang; Z. J. Cheng; X. P. Guo (Theoretical and Applied Genetics, 2006)

MULTIPLE INITIAL CULTURE CONDITIONS ENHANCE THE ESTABLISHMENT OF CELL LINES FROM PRIMARY OVARIAN CANCER SPECIMENS - CARA C. BERTOZZI; CHENG-YI CHANG; SONYA JAIRAJ; XIAOCHUAN SHAN; JIA HUANG; BARBARA L. WEBER; CHRISTINA S. CHU; RICHARD G. CARROLL (In Vitro Cellular & Developmental Biology - Animal, 2006)

Multiple Initial Culture Conditions Enhance the Establishment of Cell Lines from Primary Ovarian Cancer Specimens - Cara C. Bertozzi; Cheng-Yi Chang; Sonya Jairaj; Xiaochuan Shan; Jia Huang; Babara L. Weber; Christina S. Chu; Richard G. Carroll (In Vitro Cellular & Developmental Biology - Animal, 2006)

A catalog of nonsynonymous polymorphism on mouse Chromosome 16 - Jeffrey M. Kidd; Karrie C. Trevarthen; David L. Tefft; Ze Cheng; Michaele Mooney; Mark D. Adams (Mammalian Genome, 2005)

Use of convalescent plasma therapy in SARS patients in Hong Kong - Y. Cheng; R. Wong; Y. O. Y. Soo; W. S. Wong; C. K. Lee; M. H. L. Ng; P. Chan; K. C. Wong; C. B. Leung; G. Cheng (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Increased Production and Excretion of Urea in the Kuruma Shrimp (Marsupenaeus japonicus) Exposed to Combined Environments of Increased Ammonia and Nitrite - S.-Y. Cheng; W. C. Lee; L. W. Shieh; J.-C. Chen (Archives of Environmental Contamination and Toxicology, 2004)

Lymphocyte surge as a marker for immunorestitution disease due to Pneumocystis jiroveci pneumonia in HIV-negative immunosuppressed hosts - V. C. C. Cheng; I. F. N. Hung; A. K. L. Wu; B. S. F. Tang; C. M. Chu; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Effect of organophosphorus hydrolysing enzymes on obidoxime-induced reactivation of organophosphate-inhibited human acetylcholinesterase - S. Herkenhoff; L. Szinicz; V. K. Rastogi; T.-C. Cheng; J. J. DeFrank; F. Worek (Archives of Toxicology, 2004)

Effects of Four Metals on the Degradation of Purified Terephthalic Acid Wastewater by Phanerochaete chrysosporium and Strain Fhhh - J. Yan; S. P. Cheng; X. X. Zhang; L. Shi; C. J. Zhu (Bulletin of Environmental Contamination and Toxicology, 2004)

Effect of Addition of Sodium Hydroxide and Calcium Nitrate on Polycyclic Aromatic Hydrocarbon Emission from Benzene Incineration - S. Y. Cheng; Y. L. Wei; C. J. Wu (Bulletin of Environmental Contamination and Toxicology, 2003)

Peripartum Tuberculosis as a Form of Immunorestitution Disease - V. C. C. Cheng; P. C. Y. Woo; S. K. P. Lau; C. H. Y. Cheung; R. W. H. Yung; L. Y. C. Yam; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Use of Chitosan Membrane from the Carapace of the Soldier Crab Mictyris brevidactylus for Biosensor Construction - Bo-Chuan Hsieh; Tzong-Jih Cheng; Tzu-Yu Wang; Richie L. C. Chen (Marine Biotechnology, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

Illumination and turbidity effects on observing faceted bottom elements with uniform Lambertian albedos - Kendall L. Carder; Cheng-Chien Liu; Zhongping Lee; David C. English; James Patten; F. Robert Chen; James E. Ivey; Davis Curtiss O. (Limnology and Oceanography, 2003)
Aircraft images were collected near Lee Stocking Island (LSI), Bahamas, with wavelike features for bright sand bottoms during times when solar zenith angles were large. The image contrast between leading and trailing wave facets approached a 10–15% difference because of algae accumulations in wave troughs or topographic variations of the bottom. Reflectance contrast for blue light was greater than for red and green wavelengths when algae or detritus was present in the troughs. However, the contrast at green and red wavelengths was greater than at blue wavelengths when caused by the interplay between bottom topography and oblique illumination. A three‐dimensional backwards Monte Carlo (BMC) model was developed to evaluate the effect of oblique illumination on wavelike topographic features for various values of water clarity and bottom albedo. An inverse optical modeling approach, previously developed for flat, horizontally homogeneous bottoms, was applied to the BMC results. Bathymetric estimates for bright facets tilted 10° toward the sun were slightly smaller than actual depths, whereas shaded facet depth estimates were too high by about 5%. Larger errors were associated with albedo retrievals, where shaded facets produced albedo estimates up to 15% lower than actual values. Errors increased with tilt angles up to 20° but decreased with sea and sky turbidity. Averaging sunlit and shaded pixels before running the inverse model reduced the uncertainty of bathymetric and albedo estimates to about 2 and 5%, respectively, comparable to previous field evaluations of the inversion model.

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Influences of structures on urban ventilation: A numerical experiment - Liu Huizhi; Sang Jianguo; Zhang Boyin; Johnny C. L. Chan; Andrew Y. S. Cheng; Liu Heping (Advances in Atmospheric Sciences, 2002)

Noninvasive Electrical Imaging of the Heart: Theory and Model Development - A. J. Pullan; L. K. Cheng; M. P. Nash; C. P. Bradley; D. J. Paterson (Annals of Biomedical Engineering, 2001)

Synoptic patterns in relation to ozone concentrations in west-central Taiwan - W.-L. Cheng; J.-L. Pai; B.-J. Tsuang; C.-L. Chen (Meteorology and Atmospheric Physics, 2001)

Corrosion Properties of Nanocrystalline Co–Cr Coatings - D. Cheng; V. L. Tellkamp; C. J. Lavernia; E. J. Lavernia (Annals of Biomedical Engineering, 2001)

Cellulitis Complicating Lymphoedema - P. C. Y. Woo; P. N. L. Lum; S. S. Y. Wong; V. C. C. Cheng; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Field evaluation of a passive sampler for the exposure assessment of 2-methoxyethanol - T.-S. Shih; C.-Y. Chen; R.-I. Cheng; L.-J. Wu (International Archives of Occupational and Environmental Health, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Identification and purification of a spinach chloroplast DNA-binding protein that interacts specifically with the plastid psaA - psaB - rps14 promoter region - M. C. Cheng; S. P. Wu; L. F. O. Chen; S. C. G. Chen (Planta, 1997)

Identification of Anguilla japonica and A. mavmovata elvers by allozyme electrophoresis - S. C. Lee; S. C. M. Tsoi; H. L. Cheng; J. T. Chang (Journal of Fish Biology, 1997)
In Taiwanese waters, the morphologically similar elvers of Anguilla japonica and A. marmorata can be distinguished easily at the following loci examined: CK‐D *, LDH‐B *, sMDH‐A * and sMDH‐B *. Among these, CK‐D * and LDH‐B * have fixed allelic differences which can be used as a synoptic key for easy discrimination of the elvers of these two species.

Method for quantitating cholesterol in subfractions of serum lipoproteins separated by gradient gel electrophoresis - M. -L. Cheng; C. M. Kammerer; W. F. Lowe; B. Dyke; J. L. VandeBerg (Biochemical Genetics, 1988)

Method for quantitating cholesterol in subfractions of serum lipoproteins separated by gradient gel electrophoresis - M. -L. Cheng; C. M. Kammerer; W. F. Lowe; B. Dyke; J. L. VandeBerg (Biochemical Genetics, 1988)